Pengaruh Permainan Kartu Gizi Terhadap Perubahan Pengetahuan dan Sikap Gizi Pada Siswa Sekolah Dasar - NUR AFRA, GHINA; Laras Sitoayu; Vitria Melani (UNIVERSITAS NGUDI WALUYO, 2021)
Multiple nutrition problems become a major problem for most Indonesians, including school-aged children. This nutritional problem will certainly impact on the declining quality of human resources (HR) of Indonesia in the present and future. Lacks of nutrition knowledge or lacks applying nutritional knowledge in daily life can lead to nutritional problems. One way that can be done to improve knowledge about balanced nutrition of school children, namely through the process of nutrition education. Media is one component of the process of nutrition education, media is not only serves as a complement as information giver, but the media has the function of attention that has the power to attract attention. The purpose of this research is to examine the effect of giving flash card media to change the knowledge and attitude of balanced nutrition on 5th grade students in Tanjung Duren Selatan 01 Pagi Elementary School. Total sample in this research are 86 people with Quasy Experiment design. Statistical test using t-test dependent, t-test independent and Mann-Whitney. The result of the research showed the change of knowledge and attitude of the students to the balanced nutrition after giving the flash card media intervention (pâ‰¤0,05). Flash card media has an effect on the knowledge and attitude of balanced nutrition on Tanjung Duren Selatan 01 Pagi Elementary School students. Development of nutrition education materials using flash card are needed such as the clean and healthy behaviour and food safety. Abstrak Masalah gizi ganda masih menjadi permasalahan utama bagi sebagian besar penduduk Indonesia, termasuk anak usia sekolah. Masalah gizi ini tentunya akan berdampak pada semakin menurunnya kualitas sumber daya manusia (SDM) Indonesia di masa sekarang dan mendatang. Pengetahuan gizi yang kurang atau kurangnya menerapkan pengetahuan gizi dalam kehidupan sehari-hari dapat menimbulkan masalah gizi. Salah satu cara yang dapat dilakukan untuk meningkatkan pengetahuan mengenai gizi seimbang anak sekolah, yaitu melalui proses pendidikan gizi. Media merupakan salah satu komponen dari proses pendidikan gizi, media tidak hanya berfungsi sebagai pelengkap yaitu pemberi informasi, namun media mempunyai fungsi atensi yaitu memiliki kekuatan untuk menarik perhatian. Tujuan penelitian untuk mengetahui pengaruh pemberian media kartu bergambar terhadap perubahan pengetahuan dan sikap gizi seimbang pada siswa kelas V SDN Tanjung Duren Selatan 01 Pagi. Sampel 86 orang dengan desain Quasy Experiment. Uji statistik menggunakan t-test dependent, t-test independent dan Mann-Whitney. Hasil penelitian menunjukkan adanya perubahan pengetahuan dan sikap siswa terhadap gizi seimbang setelah diberikan intervensi media kartu bergambar (pâ‰¤0,05). Pemberian media kartu bergambar berpengaruh terhadap pengetahuan dan sikap gizi seimbang anak sekolah pada siswa SDN Tanjung Duren Selatan 01 Pagi. Perlu diadakan pengembangan materi pendidikan gizi menggunakan media kartu bergambar seperti materi PHBS dan keamanan pangan